Implicit associations to infant cry : genetics and early care experiences influence caregiving propensities - Senese, Vincenzo Paolo (2019)
Adults' sensitive appraisal of and response to infant cry play a foundational role in child development. Employing a gene × environment (G × E) approach, this study investigated the interaction of genetic polymorphisms of the serotonin transporter gene (5-HTTLPR) and oxytocin receptor genes (OXTR; rs53576, rs2254298) with early parental care experiences in influencing adults' implicit associations to infant cry. Eighty nulliparous adults (40 females, 40 males) responded to the Parental Acceptance-Rejection Questionnaire (PARQ), a measure of early care experiences, and participated in a Single Category Implicit Association Task (SC-IAT) to measure implicit associations to infant cry. Independent of parental experience, the valence of the implicit response to infant cry is associated with the serotonin transporter gene polymorphism (5-HTTLPR), with LL-carriers showing more positive implicit associations than S-carriers. OXTR rs53576 moderated the relation between parental rejection and implicit appraisal of infant cry: A-carriers who experienced negative early care showed an implicit positive appraisal of infant cry, whereas in GG carriers, positive early care experiences were associated with an implicit positive reaction to infant cry. OXTR rs2254298 had no relation to implicit associations to infant cry or to early care experiences. These findings cast light on the possible interplay of genetic inheritance and early environment in influencing adults' responses to infant cry that may be incorporated into screening protocols aimed at identifying at-risk adult-infant interactions.